Antibacterial Activity of Organic Solvents Extract on Fruits and Leaves of Black Mulberry against Streptococcus Mutans and Lactobacillus Acidophilus - G. M. Prashant; Shivanand Dharwad; M. Reshma; Vidya K. Lohe; Smita Pattanshetty; Anurag Bhatnagar; Kumar G. Chhabra; Priyanka P. Madhu (Journal of Pharmacy and Bioallied Sciences)
Background: The mulberry leaves have far more flavonoids than other berries while having much less catechin. The aim and objective of this study were assessment of the antibacterial efficacy of ethanolic extract of mulberry fruit and leaves on Streptococcus mutans and Lactobacillus acidophilus. Material and Methods: The ethanol extracts of fruits and leaves of black mulberry will be prepared in the institute. The minimal inhibition concentration will be determined against the Streptococcus mutans and Lactobacillus acidophilus. Results: A 25% mulberry leaves and 100% mulberry fruit have shown less Streptococcus mutans and Lactobacillus count. A concentration of 25% mulberry leaves has shown less Streptococcus mutans count. A concentration of 25% mulberry leaves and 100% mulberry leaves has shown no lactobacillus count. Conclusions: The results indicated that phenolics and flavonoids exerted a noteworthy influence in antioxidant examinations, given that the quantities of these compounds were directly proportional to the level of activity observed.